2021
DOI: 10.3390/coatings11111370
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Oil Enriched with Antioxidants Extracted from Watermelon (Citrullus colocynthis) Skin Sap and Coated in Hydrogel Beads via Ionotropic Gelation

Abstract: Many plants and fruits are rich in antioxidant and antimicrobial compounds, such as phenolic compounds. Watermelon is one example, as various parts of the fruit present interesting phytochemical profiles. This study demonstrates that a natural C. colocynthis (watermelon) (W) skin sap (SS) extract can effectively improve the oxidative stability of microencapsulated soybean (SB) oil. By employing a combination of alginate–xanthan gums (AXG) in a matrix hydrogel bead model with WSS extract, high encapsulation eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Extraction is the most commonly used method. For example, the extract of watermelon rind is rich in antioxidant substances, which can effectively increase the stability of soybean oil, thereby prolonging its shelf life oil [44].…”
Section: Artificial Antioxidants 221 Antioxidants Purified By Artific...mentioning
confidence: 99%
“…Extraction is the most commonly used method. For example, the extract of watermelon rind is rich in antioxidant substances, which can effectively increase the stability of soybean oil, thereby prolonging its shelf life oil [44].…”
Section: Artificial Antioxidants 221 Antioxidants Purified By Artific...mentioning
confidence: 99%
“…In general, low oxidative stability is due to a major problem, known as oxidation. This induces oil quality deterioration, and it leads to health problems like colds, cancer, heart disease, mutagenicity, and other diseases [ 96 ]. In order to preserve the high nutritional value of oils and improve their oxidative stability and their shelf life, many approaches are used.…”
Section: Enrichment Of Oils With Natural Antioxidantsmentioning
confidence: 99%
“…Several studies have been previously carried out with plant extracts to prevent oxidative deterioration. Among them, olive leaves [ 118 ], some aromatic plants [ 119 ], rosemary, rambutan, fruit peel [ 120 ], grape seed [ 121 ], cocoa bean shell [ 122 ], coffee husk [ 123 ], peanut skin [ 124 ], Cressa cretica L. leaves [ 125 ], goji berry [ 126 ], marjoram, thyme, ginger, turmeric [ 127 ], oregano [ 15 ], watermelon [ 96 ]. It has been shown that soybean oil enriched with olive leaf extract showed lower peroxide value and a lower amount of secondary product compared to the control [ 118 ].…”
Section: Enrichment Of Oils With Natural Antioxidantsmentioning
confidence: 99%
“…Antioxidants as health-promoting food components have been discussed in nutrition science for several years ( 6 8 ). The natural or enriched content of antioxidants is associated with health and disease prevention ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%